Then
Ok need to find the inverse and i need to show that
f ^(-1) o f= x= f o f^(-1)
p(x) =
x
-----
x - 1
i did
y=
x
---
y -1 = (y-1) x = y then xy -1x = y -xy
then
-1x = y(-x)
----- -------
-x -x
which means x = y ?
then i guess i need to find the inverse of that? i dont get it?
the inverse of x =y is y=x ?? i'm lost???
Hello, b_austintx!
Your algebra is off . . .
Find the inverse and verify that: .
. .
We have: .
Switch variables: .
Solve for
. . Factor: .
Therefore: .
. . Interesting . . . p(x) is its own inverse!
~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~ ~
We will verify that: .
Multiply by
. . Done!